Penyuluhan Manfaat Rumput Laut untuk Perawatan Kulit Wajah pada Masyarakat Kecamatan Muara Gembong - Supiani, Titin; Ayuningtyas, Nurina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Muara Gembong sub-district has a high level of suitability for seaweed cultivation because it is included in the category of areas with high salinity, currents, and sufficient substart. The people of Muara Gembong sub-district use it as a place to cultivate the seaweed species Gracilaria sp. The purpose of this service is to increase community knowledge and skills in utilizing seaweed as a facial skin beauty mask. The method used was counseling to teachers and guardians of SDN 03 Pantai Mekar students. The training was attended by 8 teachers and 5 student guardians. Evaluation was carried out to measure the satisfaction of service activities using a questionnaire containing 4 indicators, namely quality and productivity, material, instructor, and satisfaction. The overall results showed that 77% of participants were very satisfied with the service activities, and 23% were satisfied. It can be concluded that the participants were very satisfied with the service activities carried out by the lecturers of the Cosmetics and Beauty Care Study Program.